The Effect Of The Problem-Based Learning Model On Eighth-Grade Students’ Reading Comprehension Of Explanatory Texts - Callista Azalia Nur Firdaus; Agus Milu Susetyo; Syahrul Mubaroq (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to determine the effect of the Problem Based Learning model on students' reading comprehension of explanatory texts in grade VIII at SMP Negeri 7 Jember. This research employed a quantitative approach using a quasi-experimental design with a pretest and posttest structure. The sample consisted of three classes, each comprising 30 students. The instrument used was a reading comprehension test administered before and after the learning treatment. Data were analyzed using the Shapiro-Wilk normality test and paired samples t-test to identify differences between pretest and posttest scores. The results showed a significant increase in posttest scores across all classes, with significance values less than 0,05. These findings indicate that the Problem Based Learning model has a positive impact on students' reading comprehension of explanatory texts. Problem based learning encourages students to actively engage in reading activities, understand the structure of the text, and identify key information. Therefore, the PBL model can be considered an effective instructional approach for improving students' reading comprehension abilities at the junior high school level.